Influence of large solar power plant on short-circuit currents and analysis of operation of distance protection system of high-voltage connection line - Sučević, Nikola J. (Proceedings, Electrical engineering institute "Nikola Tesla", 2018)
The focus of this paper is the analysis of the operation of the solar power plant in the emergence of short-circuits on high-voltage line that connects the power plant to the transmission network. The paper analyzes the response of the solar power plant in the event of a fault on line and the contribution to the short-circuit currents. The operation of the relay protection system of the transmission line has been analyzed, taking into account the characteristics of the short-circuit currents of the solar power plant and the contribution of the transmission network. Additionally, suggestions have been provided for the setting of protective functions to allow adequate response to the protection system. Network modeling and analysis were performed using the DlgSILENT PowerFactory software package.